OLFM4 mediating ischemia/reperfusion-induced kidney injury by regulating renal tubular epithelial cells ferroptosis via GPX4 - Zehao Zhang; Yaqi Wang; Zhiqiang Mu; Sheng Zhao; Tingting Zhang; Ziqi Zhang; Shiren Sun; Ming Bai (Molecular Biology Reports, 2026)

Deciphering mechanisms of environmental adaptation, antibiotic tolerance, and potential virulence traits of Pseudomonas baetica isolated from anthropogenic habitat - Mu-Qi Zhang; Yi-Cheng Wang; Ming-Ying Mao; Yin-Qiu Qin; Peng Yan; Hui-Min Fu; Yuan-Xiang Mao; Ji-Cheng Liu; You-Peng Chen; Meng-Jiao Gao (Journal of Environmental Chemical Engineering, 2026)

Reaction engineering of a solar chimney-driven honeycomb photocatalytic reactor for outdoor low concentration methane oxidation - Hanbing Xiong; Tingzhen Ming; Yongjia Wu; Liwen Mu; Renaud de Richter; Wenting Lin; Wenyu Li; Chong Peng; Wei Li (Chemical Engineering Journal, 2026)

A dual colorimetric and fluorescent sensor for non-enzymatic glucose detection via catalytic reaction with o-phenylenediamine mediated by carbon dot-decorated Fe3O4 nanoparticles - Wei-Bin Tseng; Wei-Kai Tsai; Ming-Mu Hsieh; Chi-Yu Lu; Po-Chiao Lin; Wei-Lung Tseng (Analytica Chimica Acta, 2026)

Integrating network pharmacology, molecular dynamics, and in vitro assays to unveil the mechanism of costunolide against gastric cancer - Chaohong Zhu; Qiuxiong Chen; Ying Li; Hui Wu; Qijun Ming; Mengyue Ma; Junjie Mu; Xiaoqin Long; Xian Yang; Xue Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

A surface-engineered mycelial biofilm incorporating a self-cascading nanozyme for mycotoxin degradation in edible oils - Xue-ming Cao; Xue-ting Zhu; Yang-yang Geng; Ruo-mu Xia; Jin-min Zhang; Li-na Wu (Chemical Engineering Journal, 2026)

Iron oxide catalytic pyrolysis and iron oxide-steam catalytic gasification of epoxy resin: Mechanistic insights from experiments, ReaxFF MD and DFT - Meng Sun; Hongxin Liang; Zhen Wang; Jianbiao Chen; Yan Shang; Ming Dong; Liang Wang; Lin Mu (Chemical Engineering Journal, 2026)

Development and application of KASP molecular marker for accelerated breeding of low-acid Cerasus humilis cultivars - Xia-Yu Xing; Xiao-Yan Wang; Yue-Zhan Xiao; Hao-Nan Wang; Hou-Qiang Song; Ming Liu; Xiao-Peng Mu; Jian-Cheng Zhang; Lu-Ting Jia; Yu Gary Gao; Shuai Zhang; Peng-Fei Wang (Plant Cell Reports, 2026)

Plasma-activated O-Nd2WO6/f-CNF hybrid electrode for sensitive electrochemical detection of azathioprine in environmental water samples - Kumar Gokulkumar; Parthasarathi Manimaran; Shen-Ming Chen; Neeraja Bose; Shih-Hsuan Chen; Kun-Mu Lee (Journal of Environmental Chemical Engineering, 2026)

K isotope behavior in topsoil from the southeastern margin of the Tibetan Plateau - Yanan Cheng; Jun Mu; Peizheng He; Cheng Cao; Shichao An; Can Zhang; Xiaoping Feng; Cheng Zhao; Xiao-Ming Liu (Geochimica et Cosmochimica Acta, 2026)

Biodegradable polybutylene adipate terephthalate packaging with dual-functionality: Synergistic effects of curcumin coating and laser micro-perforation on sweet cherry preservation - Zhijie Zuo; Xiao Chen; Ming Li; Xinhua Zhang; Binshan Mu; Yijing Li; Zhanjun Guo; Changfeng Zhang; Xinguang Fan; Fujun Li; Fengjun Guo (Food Packaging and Shelf Life, 2026)

Coupled influence of Western Pacific moisture anomalies and mid-tropospheric humidity on October precipitation in Yunnan Province Southwest China - Wen-Jun Sun; Zhen-Peng Tao; Zi-Yang Zhang; Tian-Qing Lan; Taohui Li; Peng Zi; Jian Zhang; Yao Wu; Ming-Qiang Liang; Chao-Jun Chen; Yuan-Yuan Mu; Jun-Yun Li; et al. (Atmospheric Research, 2026)

Research perspectives and micropropagation of Cardioteucris cordifolia C. Y. Wu - Mu Ze; Binyue Zhang; Haoyu Ma; Zhun Sun; Ming Dong; Lijuan Zou (In Vitro Cellular & Developmental Biology - Plant, 2026)

Grass carp pyruvate kinase PKM acts as a key viral helper by orchestrating NS80-mediated VIB formation and multifaceted inhibition of the RLR-IFN-STAT1 antiviral cascade - Mu Niu Yang; Yang Chen; Ming Xian Chang (Fish & Shellfish Immunology, 2026)

Chronic ammonia stress inhibits growth in juvenile yellow catfish (Pelteobagrus fulvidraco) through intestinal nutrient assimilation interference - Yan-jie Tang; Mu-zi Zhang; Ming Li (Aquaculture, 2026)

Simultaneous remediation of heavy metals in mining soil using nZVI-supported attapulgite - Jun Ren; Caili Tong; Hanru Ren; Ming Gao; Gui Ma; Yunmeng Li; Rui Zhu; Xuri Mu; Chun Yang; Ling Tao (Environmental Geochemistry and Health, 2026)

Targeting ACSL4: A potential strategy to alleviate deoxynivalenol-mediated intestinal ferroptosis, oxidative stress, and immunosuppression in Channa argus - Yi-Ran Zhao; Tong-Hao Wang; Ze-Xin Zhao; Xiao-Tian Niu; Hong-Ming Lv; Yan-Bing Li; Yang Cao; Mu-Yang Li (Aquaculture, 2026)

Trace carbonyls in water reuse: Structure-dependent multi-barrier penetration and enhanced deep mineralization via dual-radical oxidation synergism - Yun-Peng Wu; Qian-Yuan Wu; Zi-Bo Jing; Yu-Ming Tian; Jiang-Lei Xiong; Mu-Da Han; Sheng-Mei Li; Er-Dong Wang; Wen-Long Wang (Water Research, 2026)

Chronological and climatic insights from Karst Cave Silt Sediment in Southwest China - Yuan-Yuan Mu; Qing-Duo Wang; Chang-Sheng Wang; Tian-Zhou Zhang; Shao-Qin Ma; Jing-Ming Yang; Hai-Cheng; Wen-Jun Sun; Jun-Yun Li; Yan-Min Dong; Lu-Peng Yu; Ting-Yong Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

A robust system for somatic embryogenesis and shoot organogenesis in Begonia grandis subsp. sinensis (A. DC.) Irmsch and genetic fidelity assessment of the regenerants - Feimin Ma; Zhengli Shan; Haonan Su; Ruijing Han; Wenjing Zhou; Mu Ze; Ming Dong; Qinggui Wu; Lijuan Zou (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

First Report on the Asexual Morphology of Nigrograna jinghongensis (Nigrogranaceae, Pleosporales) with a New Host Record from China - Li‐Xue Mi; Hai‐Yan Song; Kevin D. Hyde; Prapassorn D. Eungwanichayapant; Ausana Mapook; Mu‐Sen Chen; Dian‐Ming Hu (New Zealand Journal of Botany, 2026)
Nigrograna jinghongensis was originally described based on sexual morphology from decaying woody litter in Yunnan Province, China. In this study, we report its asexual morph, isolated as endophytes from Tetradium ruticarpum in Anhui Province. The asexual morph of N. jinghongensis features coelomycetous pycnidia that are dark brown and globose to pyriform, bearing filiform, septate conidiophores with phialidic, hyaline conidiogenous cells, and ellipsoidal to subcylindrical, aseptate, guttulate conidia. Species identification was confirmed by multigene phylogenetic analysis using ITS, LSU, SSU, tef1‐α , and rpb2 sequences. This is the first report of the asexual morph of N. jinghongensis , expanding knowledge of its life cycle, ecological adaptability, and host association.

Phosphogypsum as a soil amendment: Research on the conversion of phosphorus, fluorine, and environmental risk assessment - Ming Yang; Mu Li; Linhu Li; Jiayu Mao; Le He; Dongmei Wang; Zhengjun Gong (Journal of Environmental Chemical Engineering, 2026)

Reaction mechanisms of coal gasification in supercritical water with CO2 transport agent: A ReaxFF molecular dynamics study - Ruiqi Mu; Ming Liu; Jingqi Gao; Kai H. Luo; Junjie Yan (Fuel, 2026)

Dehydrocostus lactone induces apoptosis and mitophagy in gastric cancer cells through the ROS-mediated mitochondrial pathway - Qiuxiong Chen; Ying Li; Junjie Mu; Qian Ming; Chaohong Zhu; Ziyue He; Mengyue Ma; Xiaoqin Long; Hui Wu; Baoli Qiu; Lihe Zhang; Xian Yang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

A lightweight detection algorithm for cereal weed recognition based on deep learning - Xiao-Wei Dong; Lin-Feng Wang; Xi-Mu Zhang; Ming Wang; Wei-Kai Li (Crop Protection, 2026)

Observation of out-of-plane ferroelectricity in ∼5 nm ultrathin SrBi2Ta2O9 films for memristors and synapses application - Li-Ping Tan; Xue-Feng Hu; A-Long Li; Wei-Wei Qing; Ming Zhou; De-Bao Yu; Guo-Peng Zhang; Qing-Qing Mu; Zi-Long Wang; Xiao-Liang Wang; Ya-Li Bi; Wei Zhang (Chemical Engineering Journal, 2026)

Comprehensive assessment of secondary metabolite diversity and in vitro anti-diabetic properties in Sanghuangporus quercicola cultured under different conditions - Mingxing Yu; Na Zhang; Xiaofeng Ma; Xiaoshuang Zhou; Shude Yang; Weihang Peng; Yin Li; Yuejun Mu; Xianhao Cheng; Rui Zhang; Yongfei Ming (Systems Microbiology and Biomanufacturing, 2026)

Microscopic probing into plasmodesmata (PD) and PD-derived intercellular gateways (PdIGs): Beyond morphology - Ming-fang Lv; Wei-na Shang; Yuan-xing Dai; Jun-ying Li; Yi Li; Shuai Fu; Jian Hong; Li Xie; Heng-Mu Zhang (Protoplasma, 2026)

Spatio-temporal inversion of surface soil organic matter in the Hexi Corridor based on remote sensing data and multiple model integration - Lei Zhang; Xia Jia; Yonghua Zhao; Qi Mu; Lishan Shan; Ming Zhao; Shaocheng Si (CATENA, 2025)

Genome-Wide Identification and Expression Analysis of β-Ketoacyl-CoA Synthase Family in Sugarcane (Saccharum spontaneum) - An-zi Li; Xin Peng; Yuan Huang; Zhao-fu Bi; Ming-jing Liao; Mu-qing Zhang; Sheng-hua Xiao (Tropical Plant Biology, 2025)

Study on the mechanism of costunolide inhibiting triple-negative breast cancer by EGFR ubiquitination and degradation to suppress the ERK/AKT signaling pathway - Ying Li; Junjie Mu; Qiuxiong Chen; Qian Ming; Chaohong Zhu; Yujie Xiao; Baoli Qiu; Xue Zhang; Baoshun Zhang; Xian Yang (Journal of Molecular Histology, 2025)

Transforming residual biomass of Irish red seaweed Asparagopsis taxiformis and Palmaria palmata into biosorbents for methylene blue adsorption - Weihao Meng; Ruipeng Zhang; Siwei Gu; Ming Zhao; Jiani Luo; Colm P. O'Donnell; Yuan Li; Hongnan Sun; Taihua Mu; Marco Garcia-Vaquero (Algal Research, 2025)

Downlisting and recovery of species assessed by the IUCN - Mu‐Ming Lin; Richard A. Fuller; In‐Ki Kwon; Kisup Lee; Simba Chan; Wangwang Qiu; Yat‐Tung Yu; Chi‐Yeung Choi (Conservation Biology, 2025)
Despite the increasing number of species assessed for extinction risk by the International Union for Conservation of Nature (IUCN) (163,040 species as of 2024), only about 1 in 1,000 have been downlisted due to genuine population improvement. Although this rare conservation achievement has been widely celebrated in several recent cases, some other downlisting decisions have met with controversy. A primary role of the IUCN is to assess extinction risk. In this role, it must maintain its independence and not be influenced by the public outcry that may occur when a high‐profile species is downlisted, even if well‐established conservation programs may be disrupted or abandoned as a result. We explored the potential positive and negative consequences of downlisting for conservation efforts through case studies of the giant panda ( Ailuropoda melanoleuca ), red‐crowned crane ( Grus japonensis ), saiga antelope ( Saiga tatarica ), and black‐faced spoonbill ( Platalea minor ), which has recently been proposed for downlisting. Although downlisting can enable more effective use of limited resources, these cases highlight potential risks, including weakened legal backing, diversion of resources away from the species, and declining public and political support. The relatively unquestioned downlisting of the saiga antelope illustrates how early and inclusive engagement of local experts, assessors, donors, and other stakeholders can help ensure that decisions are effectively communicated and implemented without jeopardizing species recovery. The IUCN Green Status of Species assessment is a complementary tool to the IUCN Red List and offers a useful measure of conservation progress, which can help decision makers ensure that downlisting does not undermine long‐term conservation efforts.

Utilizing air discharge to preserve post-harvest quality of lotus root by suppressing fusarium oxysporum - Pengyue Zhang; Huizhi Chen; Ben Niu; Honglei Mu; Ruiling Liu; Yanchao Han; Ming Yin; Chaoyi Shen; Haiyan Gao; Hangjun Chen (Food Chemistry, 2025)

Why not use tertiary amines to prepare anion-exchange membranes for desalination with electrodialysis? - Shuaijun Yu; Yixiang Yu; Yan Zhang; Yangbo Qiu; Tong Mu; Ming Li; Zhipeng Xu; Qiang Wei; Jiangnan Shen (Chemical Engineering Journal, 2025)

Exploring the interaction between vermicompost application and soil types on the dispersal of antibiotic resistome above- and belowground - Meirui Mu; Keqiang Zhang; Ming Yang; Bingjun Han; Yutao Sun; Fengxia Yang (Applied Soil Ecology, 2025)

Dysfunction of cerebrospinal fluid circulation and neurovascular decoupling in end-stage renal disease patients with mild cognitive impairment - Zhaoyao Luo; Lurui Bo; Xinyi Zhu; Qiange Zhu; Huijie Yuan; Wen Gu; Peng Li; Yihao Peng; Xiang Chen; Ming Zhang; Shaohui Ma; Junya Mu (GeroScience, 2025)
End-stage renal disease (ESRD) patients frequently experience mild cognitive impairment (MCI), which significantly affects their quality of life. Although dysfunctions in cerebrospinal fluid (CSF) circulation and neurovascular coupling (NVC) have been implicated in cognitive impairment, their interrelationship remains unclear. This study aimed to investigate the association between CSF circulation dysfunction and NVC disruption in ESRD patients with MCI. We enrolled 68 ESRD patients with MCI and 65 healthy controls (HCs). CSF circulation was assessed using choroid plexus volume (CPV), the diffusion tensor imaging along the perivascular space (DTI-ALPS) index, and perivascular space volume fraction (PVSVF). NVC was evaluated using coupling metrics between cerebral blood flow (CBF) and resting-state functional magnetic resonance imaging (MRI) indicators: amplitude of low-frequency fluctuation (ALFF), fractional ALFF (fALFF), and regional homogeneity (ReHo). Cognitive performance was measured using a battery of neuropsychological tests. Compared to HCs, ESRD patients showed significantly increased CPV ( P < 0.001) and enlarged PVSVF ( P < 0.05), along with a decreased DTI-ALPS index ( P < 0.01). Global and regional NVC metrics were significantly reduced in ESRD patients ( P < 0.001). Moreover, regional NVC metrics were negatively correlated with CPV. Mediation analysis further revealed that CBF-ReHo coupling in the left cingulate gyrus pregenual area 32 mediated the relationship between elevated LCPV and cognitive decline. These findings suggest that CSF circulation dysfunction and impaired NVC are interrelated in ESRD-MCI. Disruption of CSF circulation may contribute to cognitive decline by impairing NVC, highlighting both as potential targets for early diagnosis and intervention in ESRD-related cognitive impairment.

Insufficient telomeric DNA damage response promotes chromosomal instability in aged oocytes - Tianqi Cao; Simiao Liu; Fang Wang; Min Gao; Wenlian Wu; Yanling Qiu; Ming Mu; Tengteng Xu; Jinkun Wen; Yuxi Chen; Haiying Liu; Xiqian Zhang; et al. (Science Bulletin, 2025)

Astaxanthin ameliorates Cr (VI) accumulation, antioxidant, digestive, apoptosis and inflammatory response - Lei Zhao; Ying Zhang; Jie Yu; Yi-Han Liu; Zhi-Hao Cai; Mu-Yang Li; Ming Liu (Regional Studies in Marine Science, 2025)

Enhanced electrochemical detection of the antibiotic levofloxacin using temperature optimized Er2MoO6 nanomaterials for environmental monitoring - Kumar Gokulkumar; Sri Balaji Natarajan; Shen-Ming Chen; Sakthivel Kogularasu; Shih-Hsuan Chen; Kun-Mu Lee (Journal of Water Process Engineering, 2025)

Development of a CD3ε mAb that can identify and in vitro activate T cells in large yellow croaker (Larimichthys crocea) - Zhichao Fang; Yi Cao; Haokai Chen; Jie Cheng; Ming Geng; Jiong Chen; Yinnan Mu; Kang Li; Jialong Yang; Xiumei Wei (Fish & Shellfish Immunology, 2025)

Ti3C2Tx/TiO2/CuO nanocomposite-based gas sensors for high-performance ethanol detection at room temperature - Ming Zhou; Xuefeng Hu; Zhiyuan Liu; Weiwei Qin; Liping Tan; Jilei Yang; Debao Yu; Qingqing Mu; Anquan Bao; Yali Bi; Wenjuan Yu; Wei Zhang (Chemical Engineering Journal, 2025)

Tailoring key intermediates and interfacial water at Ag92Ru8 aerogel toward sustainable ammonia synthesis from nitrate - Junjie Chen; Xiaomei Xing; Sisi Wen; Mengyuan Li; Di Liu; Wenji Jiang; Xinyi Shao; Ruikai Qi; Yumei Yang; Ming Mu; Zheng-jie Chen; Bing Zhao; et al. (Chemical Engineering Journal, 2025)

Preface to the Special Issue Commemorating the 40th Anniversary of Advances in Atmospheric Sciences and the Centenary of the Chinese Meteorological Society - Mu Mu; Junji Cao; Ming Xue (Advances in Atmospheric Sciences, 2025)

Two novel 5,5-spiroketal sesquiterpenoid isomers from the roots of Angelica biserrata (R. H. Shan &Yuan) C. Q. Yuan & R. H. Shan - Fuyong Ni; Rongrong Li; Zixian Xie; Ying Li; Ningning Xu; Xuanyu Mu; Ming Yan; Chenfeng Zhang; Zhenzhong Wang; Xue Xie; Wei Xiao (Natural Product Research, 2025)

Exploring Morphological Indicators for Ramet Age Discrimination of Fargesia nitida Based on Growth Patterns - Xiu-xin Mu; Kai-ming Lei; Hong-ou Sun; Pei-gang Kuang; Yue Zhang; Guo-lan Wang; Tao Zeng (Journal of Plant Growth Regulation, 2025)

A new phenolic compound from Persicaria capitata - Lei He; Fei Zhong; Xing-Jun Chen; Ya-Ru Yang; Xue-Long Yan; Ming-Hui He; Xu Zhang; Mu-Zhen Wang; Yong-Qin Zeng; Qin-Feng Zhu; Zhu Zeng; Bo Tu; et al. (Natural Product Research, 2025)

The impact of the circular economy pilot policy on green total factor productivity: evidence from a quasi-natural experiment in China - Liang Xie; Xian-zhong Mu; Ming-wei Li; Guang-wen Hu (Clean Technologies and Environmental Policy, 2025)

Characteristics of loess landslides under the effects of faults and rivers and their correlations with geological and surficial evolutionary processes - Qi-qi Liu; Wan-li Xie; Hui Yang; Ming Yan; Rong-sen Zhu; Ke Mu; Yi-lun Chang; Shengjie Di; Xiaoliang He; Xiaomin Liu; Ying Zhang (Bulletin of Engineering Geology and the Environment, 2025)

Facile synthesis of trimetallic compounds based on cobalt and nickel with ammonium fluoride-based complex for energy storage applications - Tsai-Mu Cheng; Pei-Chen Kuo; Yi-Chun Lai; Pin-Yan Lee; Chutima Kongvarhodom; Muhammad Saukani; Sibidou Yougbaré; Hung-Ming Chen; Kuo-Chuan Ho; Lu-Yin Lin (Journal of Environmental Chemical Engineering, 2025)

Development of cushioning-antibacterial dual-functional cellulose packaging and its application for the Chinese bayberry during simulated transportation vibration - Yifan Xue; Ben Niu; Yanchao Han; Weijie Wu; Guannan Wang; Ming Yin; Xiangjun Fang; Ruiling Liu; Hangjun Chen; Haiyan Gao; Honglei Mu (Food Packaging and Shelf Life, 2025)

Significant effects of earthworm species on antibiotic resistome in livestock manure as revealed by metagenomic analysis - Ming Yang; Liang Peng; Meirui Mu; Fengxia Yang; Zhonghan Li; Bingjun Han; Keqiang Zhang (Environmental Pollution, 2025)

Predicting and regulating potential zone for heavy metal re-contaminated farmland: Case study in Taiwan - Jieh-Haur Chen; Mu-Chun Su; Meng-Fen Yeh; Wei-Jen Lin; Tzuyang Yu; Ming-Chung Yeh (Environmental Development, 2025)

Dissolved organic matter mitigates the toxicity of silver nanoparticles to freshwater algae: Effects on oxidative stress and membrane function - Jilai Zhang; Chenglei Hu; Ming Jiang; Qianqian Xiang; Sheng Wang; Youbo Su; Naiming Zhang; Zhihao Si; Yuning Mu; Ran Yang (Environmental Pollution, 2025)

Hydroxyl-induced structural defects in metal-organic frameworks for improved photocatalytic decontamination: Accelerated exciton dissociation and hydrogen bonding interaction - Wen-Qiang Li; Yuan-Ming Li; Nannan Hou; Xiao-Guo Zhou; Yang Wang; Xian-Yang Shi; Yang Mu (Journal of Hazardous Materials, 2025)

Comparative lipidome revealed an increase of unsaturated lipids in Bifidobacterium animalis subsp. lactis 420 by linoleic acid supplementation - Qing Liao; Shuyan Wu; Ziyi Tang; Xi Yang; Ming Huang; Xing Weng; Xia Yu; Xiaoyuan Wang; Mu Zhang; Meijuan Xu; Xiaoqing Hu (Systems Microbiology and Biomanufacturing, 2025)

Thiol-linked hyaluronic acid-mediated encapsulation of RCR-stabilized gold nanoclusters for hyaluronidase sensing and cellular imaging - Manivannan Madhu; Meng-Yuan Tsai; Ming-Mu Hsieh; En-Yu Lin; Wei-Bin Tseng; Chi-Yu Lu; Wei-Lung Tseng (Carbohydrate Polymers, 2025)

Maize kernel nutritional quality—an old challenge for modern breeders - Decui Li; Anqi Hao; Wen Shao; Weiwei Zhang; Fuchao Jiao; Haiyan Zhang; Xueyan Dong; Yuan Zhan; Xia Liu; Chunhua Mu; Zhaohua Ding; De Xue; et al. (Planta, 2025)

Durable and degradable adhesive-free wood straw via cell wall activation and self-bonding - Liangxian Liu; Guoqing Mu; Haiyu Li; Haozhou Huang; Yuyan Jiang; Yutong Chen; Ming Wei; Dexiu Min; Jian Li; Yanjun Xie; Zhenqian Pang; Shaoliang Xiao (Chemical Engineering Journal, 2025)

Highly dispersed CuOx decorated ZnO photocatalyst for low-concentration methane removal - Yun Wang; Sheng Xu; Haiyuan Zhang; Yuyin Wang; Enmao Wang; Zeyu He; Jiahua Zhu; Xiaohua Lu; Lilong Zhang; Yang Bai; Kunfeng Zhao; Qingwei Gao; et al. (Journal of Environmental Chemical Engineering, 2024)

The relationships between flavor substances and microbial communities during the fermentation of Chinese traditional red sour soup - Xin Zhang; Zhenyu Wang; Xianbing Xu; Xin Mu; Baifeng Fu; Jinxiu Xu; Shuhong Ye; Ming Du (Food Bioscience, 2024)

Mirids secrete a TOPLESS targeting protein to enhance JA-mediated defense and gossypol accumulation for antagonizing cotton bollworms on cotton plants - Yu-Pei Mu; Dian-Yang Chen; Yu-Jie Liu; Ming-Yu Zhu; Xian Zhang; Yin Tang; Jia-Ling Lin; Mu-Yang Wang; Xiao-Xia Shangguan; Xiao-Ya Chen; Chengshu Wang; Ying-Bo Mao (Molecular Plant, 2024)

Investigating the effects of low-salt processing on the umami peptides of dry-cured ham using peptidomics techniques - Ming Ju; Mingxun Cui; Chunxiang Piao; Baide Mu; Jian Zhang; Lujuan Xing; Changcheng Zhao; Guanhao Li; Wangang Zhang (Food Chemistry, 2024)

A synergetic binary system of waste cooking oil-derived bio-based surfactants and its interfacial performance for enhanced oil recovery - Ming-Yue Liang; Chi Ma; Wan-Qi Qin; Homely Isaya Mtui; Wei Wang; Jin-feng Liu; Shi-Zhong Yang; Bo-Zhong Mu (Colloids and Surfaces C: Environmental Aspects, 2024)

Essential trace element and phosphatidylcholine remodeling: Implications for body composition and insulin resistance - Wen-Ling Lin; Mu-Ming Chien; Sangopas Patchara; Weu Wang; Amelia Faradina; Shih-Yi Huang; Te-Hsuan Tung; Chien-Sung Tsai; Anatoly V. Skalny; Alexey A. Tinkov; Chun-Chao Chang; Jung-Su Chang (Journal of Trace Elements in Medicine and Biology, 2024)

Multi-objective optimization of clean utilization for zinc leaching residues by rotary kiln using neural network coupled modeling - Chen-Mu Zhang; Zhi Zan; Yao Shi; Hui-Quan Li; Lang-Ming Liu; Wei-Ping Liu; Wen-Jun Lin; Jing-Jing Shi; Ying-yan Hu; Xue Guan; Kuang-Yi Chen; Xiao Liu; et al. (Journal of Cleaner Production, 2024)

GmCOL4-GmZTL1 interaction co-regulates GmSBH1 to improve seed deterioration under high temperature and humidity stress and affect leaf development - Kebin Mu; Yingjie Shu; Ming Chen; Keke Chen; Yuxin Peng; Huimin Hu; Yingzi Shen; Xi Zhang; Lifang Zhuang; Hao Ma (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Methanogenic biodegradation of thermoplastic poly(vinyl alcohol) films produced by two manufacturing processes in enrichment cultures - Ming-Le Ji; Yi-Fan Liu; Yu Bai; Zhen Hu; James H. Wang; Jia-Yi Li; Wan-Qi Qin; Lei Zhou; Shi-Zhong Yang; Ji-Dong Gu; Yingcheng Li; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2024)

Preparation, taste characterization, and evaluation of oyster composite products with increased umami and salty - Baifeng Fu; Shuzhen Cheng; Xin Zhang; Junjie Yi; Zhishen Mu; Ming Du (Food Bioscience, 2024)

Dual-Targeting EGCG/NO-Supplying protein assembled nanoparticles with Multi-Synergistic effects against atherosclerosis - Chi Lin; Tsai-Mu Cheng; Yun-Chun Liu; Fang-Yu Hsu; Chun-Ming Shih; Min-Lang Tsai; Chun-Che Shih; Fwu-Long Mi (Chemical Engineering Journal, 2024)

Exploring the novel antioxidant peptides in low-salt dry-cured ham: Preparation, purification, identification and molecular docking - Ying-dao Nan; Bai-de Mu; Chang-xin Ge; Si-qi Chen; Ming-xun Cui; Hong-mei Li; Chang-cheng Zhao; Juan Wang; Chun-xiang Piao; Guan-hao Li (Food Chemistry, 2024)

Transcriptomic and physiological analysis provide new insight into seed shattering mechanism in Pennisetum alopecuroides ‘Liqiu’ - Yue Xu; Lingyun Liu; Ming Jia; Ke Teng; Na Mu; Yidi Guo; Muye Liu; Juying Wu; Wenjun Teng; Linkai Huang; Xifeng Fan; Yuesen Yue (Theoretical and Applied Genetics, 2024)

Boosting persulfate activation through efficient π → π* transition activated by Cu ion anchored porphyrin-based metal–organic framework - Wen-Qiang Li; Oleksandr Savateev; Yuan-Ming Li; Jian-Kang Zheng; Yi-Xuan Wang; Nannan Hou; Xiao-Cheng Liu; Rong-Rong Ding; Xiao-Guo Zhou; Yang Wang; Xian-Yang Shi; Yang Mu (Chemical Engineering Journal, 2024)

Alkaloids from the stems of Fissistigma maclurei Merr. inhibit the proliferation of synoviocytes - Mu-Tao Liang; Xiao-Zheng Zhang; Zi-Hao Chen; Chuan-Shan Fu; Duo-Jiang Li; Guo-Ze Chen; Ji-Ling Yi; Xue-Ming Zhou (Natural Product Research, 2024)

Superior performance of hybrid model in ungauged basins for real-time hourly water level forecasting – A case study on the Lancang-Mekong mainstream - Zhiqiang Dong; Hongchang Hu; Hui Liu; Baoligao Baiyin; Xiangpeng Mu; Jie Wen; Dengfeng Liu; Lajiao Chen; Guanghui Ming; Xue Chen; Xiaochen Li (Journal of Hydrology, 2024)

Source apportionment and predictable driving factors contribute to antibiotics profiles in Changshou Lake of the Three Gorges Reservoir area, China - Yue Mu; Bobin Tang; Xian Cheng; Yuanhang Fu; Weibin Huang; Jing Wang; Dewang Ming; Liangshu Xing; Jinzhong Zhang (Journal of Hazardous Materials, 2024)

Physiological and transcriptomic response reveals new insight into manganese tolerance of Celosia argentea Linn. - Liyun Liang; Mu Ze; Jun Yang; Qian Xu; Cunmei Du; Xiaohong Hu; Ming Dong; Lijuan Zou; Tuo Qi (Journal of Hazardous Materials, 2024)

Enhanced Beta2-band Oscillations Denote Auditory Hallucination in Schizophrenia Patients and a Monkey Model of Psychosis - Shuo Ma; Tianzhen Chen; Wenjun Jia; Jie Liu; Shihan Ding; Puzhe Li; Hong Gan; Dapeng Zhang; Shuxin Shao; Mu-Ming Poo; Min Zhao; Bomin Sun; et al. (Neuroscience Bulletin, 2024)

Melatonin inhibits atrazine-induced mitochondrial impairment in cerebellum of mice: Modulation of cGAS-STING-NLRP3 axis-dependent cell pyroptosis - Lin Liu; Mu-Zi Li; Ming-Hui Yao; Tian-Ning Yang; Yi-Xi Tang; Jin-Long Li (Science of The Total Environment, 2024)

Cellular localization and potential ligands of a novel scavenger receptor class B/CD36 protein homolog (Pt-SRB2) identified in the marine crab, Portunus trituberculatus - Su-Ming Zhou; Fang-Mei Lin; Chang-Kao Mu; Chun-Lin Wang; Qi-Cun Zhou; Peng Sun; Fei Yin (Fish & Shellfish Immunology, 2024)

Climatic impacts of wind power in the relatively stable and unstable atmosphere: A case study in China during the explosive growth from 2009 to 2018 - Qiang Wang; Kun Luo; Xuanxuan Ming; Yanfei Mu; Shitong Ye; Jianren Fan (Journal of Cleaner Production, 2023)

Side chain modulated carbazole-based bifunctional hole-shuttle interlayer simultaneously improves interfacial energy level alignment and defect passivation in high-efficiency perovskite solar cells - Yuan-Yu Chiu; Shih-Hsuan Chen; Kun-Mu Lee; Tz-Feng Lin; Ming-Chung Wu (Chemical Engineering Journal, 2023)

3D binder-free nanoarchitecture design of porous silicon/graphene fibers for ultrastable lithium storage - Yongbiao Mu; Ruijie Zhang; Bu-ke Wu; Ming Yang; Youqi Chu; Qing Zhang; Lingfeng Zou; Xianbin Wei; Zifan Liao; Haixiang Ren; Yiju Li; Lin Zeng (Chemical Engineering Journal, 2023)

Abnormal grey matter structural changes in patients with end-stage kidney disease and mild cognitive impairment: correlations with clinical features - Huijie Yuan; Zhaoyao Luo; Wen Gu; Shaohui Ma; Guangyu Li; Dun Ding; Xueying Ma; Peng Li; Jing Yang; Xiaoling Xu; Junya Mu; Ming Zhang (Metabolic Brain Disease, 2023)
End-stage kidney disease and mild cognitive impairment (ESKD-MCI) affect the quality of life and long-term treatment outcomes of patients affected by these diseases. Clarifying the morphological changes from brain injuries in ESKD-MCI and their relationship with clinical features is helpful for the early identification and intervention of MCI before it progresses to irreversible dementia. This study gathered data from 23 patients with ESKD-MCI, 24 patients with ESKD and non-cognitive impairment (NCI), and 27 health controls (HCs). Structural magnetic resonance studies, cognitive assessments, and general clinical data were collected from all participants. Voxel-based morphometry analysis was performed to compare grey matter (GM) volume differences between the groups. The patients’ GM maps and clinical features were subjected to univariate regression to check for possible correlations. Patients with ESKD-MCI displayed significantly more impairments in multiple cognitive domains, including global cognition, visuospatial and executive function, and memory, compared to patients with ESKD-NCI. Using a more liberal threshold ( P < 0.001, uncorrected), we found that compared to patients with ESKD-NCI, patients with ESKD-MCI exhibited clusters of regions with lower GM volumes, including the right hippocampus (HIP), parahippocampal gyrus (PHG), Rolandic operculum, and supramarginal gyrus. The volumes of the right HIP and PHG were negatively correlated with serum calcium levels. ESKD-MCI was associated with a subtle volume reduction of GM in several brain areas known to be involved in memory, language, and auditory information processing. We speculate that these slight morphometric impairments may be associated with disturbed calcium metabolism.

Rapid identification of hazardous heavy metal-containing waste by combining EDXRF with machine learning: Taking zinc smelting waste as an example - Jing Teng; Yao Shi; Zuo-Hua Liu; Hui-Quan Li; Ming-Xing He; Zhi-Hong Li; Chen-Mu Zhang (Resources, Conservation and Recycling, 2023)

The regulative effect and repercussion of probiotics and prebiotics on osteoporosis: involvement of brain-gut-bone axis - Yuan-Wei Zhang; Mu-Min Cao; Ying-Juan Li; Guang-Chun Dai; Pan-Pan Lu; Ming Zhang; Li-Yong Bai; Xiang-Xu Chen; Cheng Zhang; Liu Shi; Yun-Feng Rui (Critical Reviews in Food Science and Nutrition, 2023)

Zincophile channel adjustment realizes dendrite-free zinc anode for low-temperature zinc-ion capacitors - Ming Sun; Zekai Zhang; Jin Chen; Yifan Zhang; Ruoyu Wang; Hongchun Mu; Cheng Lian; Wenqiang Wang; Gengchao Wang (Chemical Engineering Journal, 2023)

Molecular mechanism by which StSN2 overexpression inhibits the enzymatic browning of potato - Li-qin Li; Yu-lu Mu; Jing Chen; Qiang Wang; Yi-fei Lu; Sun Xin; Shi-min Yang; Xue-li Huang; Xi-yao Wang; Li-ming Lu (Postharvest Biology and Technology, 2023)

Changes in mean and extreme homogeneous precipitation in China during 1960–2020 - Yanjuan Wu; Hongli Mu; Shuang-ye Wu; Yu Xu; Ming Xu; Huawu Wu; Robin T. Clark; Chao Gao (Atmospheric Research, 2023)

Rotifer distribution patterns in relation to dissolved organic matter in the middle reaches of Huai River Basin during the dry season - Leilei Luan; Liangmin Gao; Xudong Chen; Juan Ge; Ming Mu; Xiaoqing Chen; Xinglan Zhao; Zhen Zhang; Haiqiang Zhang (Environmental Science and Pollution Research, 2023)

The health risk of acetochlor metabolite CMEPA is associated with lipid accumulation induced liver injury - Wei-Guo Wang; Mu-Yao Li; Lin Diao; Cheng Zhang; Li-Ming Tao; Wei-Xing Zhou; Wen-Ping Xu; Yang Zhang (Environmental Pollution, 2023)

Insight into the structural feature, ash transformation behavior, and alkali metal heat release characteristic of industrial lignin via experimental and equilibrium evaluation - Hongchao Yin; Xiankun Huang; Lin Mu; Xi Xi; Ming Dong; Zhaoyi Huo (Fuel, 2023)

Identification of sweet spots in shale-type and siltstone-type “shale oil systems”: A case study of the Chang 7 Member in Ordos Basin - Songqi Pan; Qiulei Guo; Caineng Zou; Zhenhua Jing; Ming Yuan; Ying He; He Zheng; Ying Mu; Zhi Yang; Shixiang Li; Xinping Zhou; Songtao Wu; et al. (Science China Earth Sciences, 2023)

Effects of solar radiation and fine roots on suction of Amorpha fruticose-vegetated soil - Han-qing Guo; Xiao-qing Chen; Dong-ri Song; Qing-yi Mu; Hamed Sadeghi; Hao Jiang; Ming Lv (Journal of Mountain Science, 2023)

Derivation of copper water quality criteria in Bohai Bay for the protection of local aquatic life and the ecological risk assessment - Yang Li; Di Mu; Hong-Qing Wu; Hai-Jiao Liu; Yong-Hui Wang; Guo-Chen Ma; Xue-Min Duan; Jian-Jun Zhou; Chun-Ming Zhang; Xing-Hua Lu; Xian-Hua Liu; Jun Sun; et al. (Marine Pollution Bulletin, 2023)

Optimizing design and performance assessment of a sustainability hydrogen supply chain network: A multi-period model for China - Miao Li; Pingwen Ming; Ran Huo; Hailin Mu; Cunman Zhang (Sustainable Cities and Society, 2023)

Targeting Senescent Tendon Stem/Progenitor Cells to Prevent or Treat Age-Related Tendon Disorders - Hao Wang; Guang-Chun Dai; Ying-Juan Li; Min-Hao Chen; Pan-Pan Lu; Yuan-Wei Zhang; Ming -Zhang; Mu-Min Cao; Yun-Feng Rui (Stem Cell Reviews and Reports, 2023)

Comparative investigation on the pyrolysis of crop, woody, and herbaceous biomass: Pyrolytic products, structural characteristics, and CO2 gasification - Lin Mu; Ranyu Wang; Pengwei Xie; Yonglin Li; Xiankun Huang; Hongchao Yin; Ming Dong (Fuel, 2023)

New (4 → 2)-abeo-clerodane diterpenoids from the Polyalthia laui and their chemotaxonomic significance - Zhang-Xin Yu; Xin-Ming Song; Mu-Yuan Li; Man-Man Zhang; Li-Zhu Huang; Xiao-Bao Li (Biochemical Systematics and Ecology, 2023)

Combined Effects of Biochar-Sedum plumbizincicola on Cadmium Concentration in Cd-Contaminated Limestone Soil and Cadmium Absorption in Lactuca sativa - Ying-Ying Liu; Wen-Min Luo; Gui-Ting Mu; Xian-Liang Wu; Zhen-Ming Zhang (Water, Air, & Soil Pollution, 2023)

The Origin and Preservation of Suspended Barites near the 90°E Ridge in the Northeastern Indian Ocean - Xuejiao Bu; Ming Liu; Yi Ding; Yadi Yang; Mu Huang; Xiaoxia Sun; Dejiang Fan; Zuosheng Yang (Journal of Ocean University of China, 2023)

Biogenetic peloidal micrites within coral skeletons cause geochemical anomalies in reef limestones, Zhongsha Atoll, South China Sea - Hong-Qiang Yang; Xi-Yang Zhang; Yue Li; Qi Shi; Shi-Chen Tao; Xi-Nan Mu; Ming-Zhuang Wang; Xiao-Ju Liu; Fei Tan; Sheng-Nan Zhou; Guan Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Doping engineering of carrier transporting layers for ambient-air-stable lead-free rudorffite solar cells prepared by thermal-assisted doctor blade coating - Kai-Chi Hsiao; Yen-Fu Yu; Ching-Mei Ho; Meng-Huan Jao; Yu-Hsiang Chang; Shih-Hsuan Chen; Yin-Hsuan Chang; Wei-Fang Su; Kun-Mu Lee; Ming-Chung Wu (Chemical Engineering Journal, 2023)

Neural Mechanism Underlying Task-Specific Enhancement of Motor Learning by Concurrent Transcranial Direct Current Stimulation - Ying Wang; Jixian Wang; Qing-Fang Zhang; Ke-Wei Xiao; Liang Wang; Qing-Ping Yu; Qing Xie; Mu-Ming Poo; Yunqing Wen (Neuroscience Bulletin, 2023)

Body mass index–based predictions and personalized clinical strategies for colorectal cancer in the context of PPPM - Yun-Jia Gu; Li-Ming Chen; Mu-En Gu; Hong-Xiao Xu; Jing Li; Lu-Yi Wu (EPMA Journal, 2022)
Currently colorectal cancer (CRC) is the third most prevalent cancer worldwide. Body mass index (BMI) is frequently used in CRC screening and risk assessment to quantitatively evaluate weight. However, the impact of BMI on clinical strategies for CRC has received little attention. Within the framework of the predictive, preventive, and personalized medicine (3PM/PPPM), we hypothesized that BMI stratification would affect the primary, secondary, and tertiary care options for CRC and we conducted a critical evidence-based review. BMI dynamically influences CRC outcomes, which helps avoiding adverse treatment effects. The outcome of surgical and radiation treatment is adversely affected by overweight (BMI ≥ 30) or underweight (BMI < 20). A number of interventions, such as enhanced recovery after surgery and robotic surgery, can be applied to CRC at all levels of BMI. BMI-controlling modalities such as exercise, diet control, nutritional therapy, and medications may be potentially beneficial for patients with CRC. Patients with overweight are advised to lose weight through diet, medication, and physical activity while patients suffering of underweight require more focus on nutrition. BMI assists patients with CRC in better managing their weight, which decreases the incidence of adverse prognostic events during treatment. BMI is accessible, noninvasive, and highly predictive of clinical outcomes in CRC. The cost–benefit of the PPPM paradigm in developing countries can be advanced, and the clinical benefit for patients can be improved with the promotion of BMI-based clinical strategy models for CRC.

Environmental impact of typical zinc smelting that implements solid waste collaborative utilization in China - Wei-Ning Liu; Yao Shi; Chen-Mu Zhang; Lang-Ming Liu; Hui-Quan Li; Bin Lu; Yuan-Bo Xie; Cai-Bei Zhuang; Tian-You Sun; Wei-Ping Liu; Xue Guan; Ying-Yan Hu (The International Journal of Life Cycle Assessment, 2022)

Recognizing and managing construction land reduction barriers for sustainable land use in China - Jia-He Zhou; Yu-Ming Zhu; Lei He; Hao-Jing Song; Bing-Xu Mu; Fen Lyu (Environment, Development and Sustainability, 2022)

Predation capacity of Bradymonabacteria, a recently discovered group in the order Bradymonadales, isolated from marine sediments - Ya Gong; Xiu-Ya Ping; Chen-Hang Zeng; Shu-Xin Wang; Yi Zhou; Ming-Yi Wang; Da-Shuai Mu; Zong-Jun Du (Archives of Microbiology, 2022)

Sestrin2 attenuates renal damage by regulating Hippo pathway in diabetic nephropathy - Yawei Bian; Chonglin Shi; Shan Song; Lin Mu; Ming Wu; Duojun Qiu; Jiajia Dong; Wei Zhang; Chen Yuan; Dongyun Wang; Zihui Zhou; Xuan Dong; et al. (Cell and Tissue Research, 2022)

GmUGT73F4 plays important roles in enhancing seed vitality and tolerance to abiotic stresses in transgenic Arabidopsis - Huimin Hu; Peipei Qian; Mengyuan Ye; Kebin Mu; Shuang Wang; Ming Chen; Hao Ma (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Growth of non‐English‐language literature on biodiversity conservation - Shawan Chowdhury; Kristofer Gonzalez; M. Çisel Kemahlı Aytekin; Seung‐Yun Baek; Michał Bełcik; Sandro Bertolino; Sjoerd Duijns; Yuqing Han; Kerstin Jantke; Ryosuke Katayose; Mu‐Ming Lin; Elham Nourani; et al. (Conservation Biology, 2022)
English is widely recognized as the language of science, and English‐language publications (ELPs) are rapidly increasing. It is often assumed that the number of non‐ELPs is decreasing. This assumption contributes to the underuse of non‐ELPs in conservation science, practice, and policy, especially at the international level. However, the number of conservation articles published in different languages is poorly documented. Using local and international search systems, we searched for scientific articles on biodiversity conservation published from 1980 to 2018 in English and 15 non‐English languages. We compared the growth rate in publications across languages. In 12 of the 15 non‐English languages, published conservation articles significantly increased every year over the past 39 years, at a rate similar to English‐language articles. The other three languages showed contrasting results, depending on the search system. Since the 1990s, conservation science articles in most languages increased exponentially. The variation in the number of non‐English‐language articles identified among the search systems differed markedly (e.g., for simplified Chinese, 11,148 articles returned with local search system and 803 with Scopus). Google Scholar and local literature search systems returned the most articles for 11 and 4 non‐English languages, respectively. However, the proportion of peer‐reviewed conservation articles published in non‐English languages was highest in Scopus, followed by Web of Science and local search systems, and lowest in Google Scholar. About 20% of the sampled non‐English‐language articles provided no title or abstract in English; thus, in theory, they were undiscoverable with English keywords. Possible reasons for this include language barriers and the need to disseminate research in countries where English is not widely spoken. Given the known biases in statistical methods and study characteristics between English‐ and non‐English‐language studies, non‐English‐language articles will continue to play an important role in improving the understanding of biodiversity and its conservation.

Stability evaluation for steep bank slope with microseismic monitoring in Three Gorges Reservoir area - Qing-ming Xie; Kui Long; Zi-mu Li; Li-chuan Chen; Hong Liu; Hong Xu; Fei He; Dan Liang; Xue-kun Xiang; Qiang Ma (Journal of Mountain Science, 2022)

A new highly oxygenated germacranolide from Carpesium nepalense var. lanatum (C.B.Clarke) Kitam - Yi-Fan Yu; Yue-Qian Li; Ru-Yue Wang; Xu Liu; Wen-Bo Cui; Xiao-Han Chen; Cheng-Mu Zhao; Feng-Ming Qi; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2022)

First report of plum bark necrosis stem pitting-associated virus affecting sweet cherry in Yunnan, China - Miao Guo; Jing Zhong; Chaowen Wang; Yue Chen; Zhengsong Yang; Tingting Li; Yongbin Wu; Yongqing Mu; Ming Ding; Jiawei He (Journal of Plant Pathology, 2022)

Study on the impact of comprehensive urbanization on urban civil building CO2 emissions in China - Rong Guo; Nan Li; Hailin Mu; Ming Zhang; Xiyue Yang; Yixuan Han; Rongkang Yao; Zhihao Shao (Environmental Science and Pollution Research, 2022)

Native herbivores indirectly facilitate the growth of invasive Spartina in a eutrophic saltmarsh - Xiao Xu; Yan Zhang; Songshuo Li; Hongyang Chen; Mu Liu; Bo Li; Ming Nie (Ecology, 2022)
Current theory (e.g., consumer‐controlled theory) predicts that nutrient enrichment typically amplifies herbivory and thereby suppresses the growth and expansion of invasive plants. Herbivores can facilitate plant regrowth in the native community by stimulating complementary growth or ameliorating habitat conditions (e.g., by increasing soil oxygen and nutrient availability), but whether they have similar positive effects on invasive plants, especially under nutrient enrichment, remains unknown. Using a field nitrogen (N)‐enrichment × crab exclusion experiment, we evaluated and compared the effects of both N enrichment and crab herbivory on the growth performance of a global invasive cordgrass, Spartina alterniflora , and a co‐occurring native plant, Phragmites australis . We found that crabs consistently suppressed P. australis by density and aboveground biomass regardless of N enrichment. In contrast, for S. alterniflora , the negative effects of crabs under ambient N were replaced by positive effects under N enrichment, with crabs stimulating complementary increases in density and aboveground biomass. The differing effects between the N treatments were driven by crab burrowing activity, which increased soil N availability, and the nutrient‐use efficiency of S. alterniflora . Our findings revealed that native herbivores can have opposing effects on native and invasive plants, which broadens our understanding of how exotic plants can achieve dominance in a changing world.

Analysis on shadow price and abatement potential of carbon dioxide in China’s provincial industrial sectors - Zhaoquan Xue; Hailin Mu; Nan Li; Ming Zhang (Environmental Science and Pollution Research, 2022)

A contribution to knowledge of Gyroporus (Gyroporaceae, Boletales) in China: three new taxa, two previous species, and one ambiguous taxon - Hui-Jing Xie; Li-Ping Tang; Man Mu; Yu-Guang Fan; Shuai Jiang; Ming-Sheng Su; Zhi-Qun Liang; Nian-Kai Zeng (Mycological Progress, 2022)

Convergence analysis of regional marginal abatement cost of carbon dioxide in China based on spatial panel data models - Zhaoquan Xue; Nan Li; Hailin Mu; Ming Zhang; Jingru Pang (Environmental Science and Pollution Research, 2021)

White matter characteristics between amygdala and prefrontal cortex underlie depressive tendency in end stage renal disease patients before the dialysis initiation - Junya Mu; Liang Ma; Dun Ding; Xueying Ma; Peng Li; Ruixiao Li; Ming Zhang; Jixin Liu (Brain Imaging and Behavior, 2021)

Flavonoids from Artemisia rupestris and their synergistic antibacterial effects on drug-resistant Staphylococcus aureus - Jiang-Er Lan; Xiao-Jin Li; Xiao-Feng Zhu; Zhong-Lin Sun; Jian-Ming He; Mire Zloh; Simon Gibbons; Qing Mu (Natural Product Research, 2021)

Proton Pump Inhibitor Exposure and Acute Myocardial Infarction Risk: A Nested Cohort Study - Hsiang-Jung Tseng; Chih-Ming Cheng; Shih-Jen Tsai; Wei-Chen Lin; Ya-Mei Bai; Chia-Fen Tsai; Tung-Ping Su; Cheng-Ta Li; Tzeng-Ji Chen; Mu-Hong Chen (Cardiovascular Toxicology, 2021)

Association of FMO3 rs1736557 polymorphism with clopidogrel response in Chinese patients with coronary artery disease - Kong-Xiang Zhu; Pei-Yuan Song; He-Li; Mu-Peng Li; Yin-xiao Du; Qi-lin Ma; Li-Ming Peng; Xiao-Ping Chen (European Journal of Clinical Pharmacology, 2021)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Genome-Wide Association Study of Plant and Ear Height in Maize - Shi Lu; Mu Li; Mo Zhang; Ming Lu; Xinqi Wang; Piwu Wang; Wenguo Liu (Tropical Plant Biology, 2020)

Interaction between shadow economy and pollution: empirical analysis based on panel data of northeast China - Jingru Pang; Hailin Mu; Ming Zhang (Environmental Science and Pollution Research, 2020)

Combined effect of polymorphisms of MTHFR and MTR and arsenic methylation capacity on developmental delay in preschool children in Taiwan - Yu-Mei Hsueh; Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Horng-Sheng Shiue; Ssu-Ning Chien; Chih-Ying Lee; Ming-I. Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2020)

Effect of using banana by-products and other agricultural residues for beef cattle in southern China - Zhulin Xue; Lan Mu; Ming Cai; Yingjun Zhang; Metha Wanapat; Bizhi Huang (Tropical Animal Health and Production, 2020)

The variation of motor-related brain structure and its relation to abnormal motor behaviors in end-stage renal disease patients with restless legs syndrome - Junya Mu; Xiaohui Liu; Shaohui Ma; Tao Chen; Xueying Ma; Peng Li; Dun Ding; Jixin Liu; Ming Zhang (Brain Imaging and Behavior, 2020)

Assessment of ramie leaf (Boehmeria nivea L. gaud) as an animal feed supplement in P.R. China - Lan Mu; Ming Cai; Zongli Wang; Jianyong Liu; Tianliang Liu; Metha Wanapat; Bizhi Huang (Tropical Animal Health and Production, 2020)

Antidepressant Drugs Correct the Imbalance Between proBDNF/p75NTR/Sortilin and Mature BDNF/TrkB in the Brain of Mice with Chronic Stress - C. R. Yang; X. Y. Zhang; Y. Liu; J. Y. Du; R. Liang; M. Yu; F. Q. Zhang; X. F. Mu; F. Li; L. Zhou; F. H. Zhou; F. J. Meng; et al. (Neurotoxicity Research, 2020)

Implementation of the Land Surface Processes into a Vector Vorticity Equation Model (VVM) to Study its Impact on Afternoon Thunderstorms over Complex Topography in Taiwan - Chien-Ming Wu; Hsiao-Chun Lin; Fang-Yi Cheng; Mu-Hua Chien (Asia-Pacific Journal of Atmospheric Sciences, 2019)

Geosites in Karamay city, Xinjiang Uygur Autonomous Region, northwest China - Jun-Ting Qiu; Liang Qiu; Hong-Xu Mu; Wen-Xin Yang; Feng Chen; Bo-Kun Yan; Jun-Chuan Yu; He-Ming Yang (Geoheritage, 2019)

Association of plasma folate, vitamin B12 levels, and arsenic methylation capacity with developmental delay in preschool children in Taiwan - Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Pui-Lam Ao; Horng-Sheng Shiue; Shiau-Rung Huang; Chien-Tien Su; Ming-I Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2019)

Astaxanthin enhances hematology, antioxidant and immunological parameters, immune-related gene expression, and disease resistance against in Channa argus - Mu-Yang Li; Xin-Yu Liu; Chang-Ge Xia; Gui-Qin Wang; Dong-Ming Zhang (Aquaculture International, 2019)

Effects of dietary Allium mongolicum Regel polysaccharide on growth, lipopolysaccharide-induced antioxidant responses and immune responses in Channa argus - Mu-Yang Li; Xin-Ming Zhu; Xiao-Tian Niu; Xiu-Mei Chen; Jia-Xin Tian; Yi-Di Kong; Dong-Ming Zhang; Lei Zhao; Gui-Qin Wang (Molecular Biology Reports, 2019)

Blockade of Endogenous Angiotensin-(1–7) in Hypothalamic Paraventricular Nucleus Attenuates High Salt-Induced Sympathoexcitation and Hypertension - Xiao-Jing Yu; Yu-Wang Miao; Hong-Bao Li; Qing Su; Kai-Li Liu; Li-Yan Fu; Yi-Kang Hou; Xiao-Lian Shi; Ying Li; Jian-Jun Mu; Wen-Sheng Chen; Wei Cui; et al. (Neuroscience Bulletin, 2019)

Base cation concentrations in forest litter and topsoil have different responses to climate and tree species along elevational gradients - Feng Xue; Ming-fei Zhao; Yu-hang Wang; Mu-yi Kang; Kai-xiong Xing; Guo-yi Wang; Jing-jing Shi; Chen Chen; Yuan Jiang (Journal of Mountain Science, 2019)

Altered amygdala-related structural covariance and resting-state functional connectivity in end-stage renal disease patients - Anmao Li; Junya Mu; Mingxia Huang; Zengjun Zhang; Jixin Liu; Ming Zhang (Metabolic Brain Disease, 2018)

Abnormal interaction between cognitive control network and affective network in patients with end-stage renal disease - Junya Mu; Tao Chen; Qianqian Liu; Dun Ding; Xueying Ma; Peng Li; Anmao Li; Mingxia Huang; Zengjun Zhang; Jixin Liu; Ming Zhang (Brain Imaging and Behavior, 2018)

Puerarin-7-O-glucuronide, a water-soluble puerarin metabolite, prevents angiotensin II-induced cardiomyocyte hypertrophy by reducing oxidative stress - Ning Hou; Bin Cai; Cai-Wen Ou; Zhen-Hui Zhang; Xia-Wen Liu; Mu Yuan; Gan-Jian Zhao; Shi-Ming Liu; Long-Gen Xiong; Jian-Dong Luo; Cheng-Feng Luo; Min-Sheng Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

Association Between Tumor Necrosis Factor-α and Diabetic Peripheral Neuropathy in Patients with Type 2 Diabetes: a Meta-Analysis - Ze-Peng Mu; Yan-Gang Wang; Cheng-Qian Li; Wen-Shan Lv; Bin Wang; Zhao-Hai Jing; Xue-Jia Song; Yu Lun; Ming-Yue Qiu; Xiao-Long Ma (Molecular Neurobiology, 2017)

Erratum to: Diurnal and seasonal variation of the elevation gradient of air temperature in the northern flank of the western Qinling Mountain range, China - Guo-yi Wang; Ming-fei Zhao; Mu-yi Kang; Kai-xiong Xing; Yu-hang Wang; Feng Xue; Chen Chen (Journal of Mountain Science, 2017)

Diurnal and seasonal variation of the elevation gradient of air temperature in the northern flank of the western Qinling Mountain range, China - Guo-yi Wang; Ming-fei Zhao; Mu-yi Kang; Kai-xiong Xing; Yu-hang Wang; Feng Xue; Chen Chen (Journal of Mountain Science, 2017)

NOX2 Mediated-Parvalbumin Interneuron Loss Might Contribute to Anxiety-Like and Enhanced Fear Learning Behavior in a Rat Model of Post-Traumatic Stress Disorder - Fang-fang Liu; Lin-dong Yang; Xiao-ru Sun; Hui Zhang; Wei Pan; Xing-ming Wang; Jian-jun Yang; Mu-huo Ji; Hong-mei Yuan (Molecular Neurobiology, 2016)

A high throughput method for rapid screening of chitosanase-producing fungal strain under acidic conditions - Su Ding; Gui-Guang Chen; Zhi-Qun Liang; Wei Zeng; Mu-Ming Cao; Guo-Pin Chen; Shu-Yu Xie; Wei Li (World Journal of Microbiology and Biotechnology, 2016)

Vascular endothelial growth factor-C protects heart from ischemia/reperfusion injury by inhibiting cardiomyocyte apoptosis - Xu-guang Chen; Yan-xia Lv; Dan Zhao; Lei Zhang; Fei Zheng; Jian-Ye Yang; Xiao-lin Li; Lu Wang; Lin-Yun Guo; Ya-mu Pan; Yu-wen Yan; Shi-You Chen; et al. (Molecular and Cellular Biochemistry, 2016)

Molecular characterization of Beclin 1 in rare minnow (Gobiocypris rarus) and its expression after waterborne cadmium exposure - Xiao-Hong Liu; Zhi-Jian Wang; Dong-Ming Chen; Mu-Fei Chen; Xing-Xing Jin; Jing Huang; Yao-Guang Zhang (Fish Physiology and Biochemistry, 2016)

Environmental Enrichment Ameliorates Neonatal Sevoflurane Exposure-Induced Cognitive and Synaptic Plasticity Impairments - Mu-huo Ji; Xing-ming Wang; Xiao-ru Sun; Hui Zhang; Ling-sha Ju; Li-li Qiu; Jiao-jiao Yang; Min Jia; Jing Wu; Jianjun Yang (Journal of Molecular Neuroscience, 2015)

Catalpol Inhibited the Proliferation of T24 Human Bladder Cancer Cells by Inducing Apoptosis Through the Blockade of Akt-Mediated Anti-apoptotic Signaling - Di Jin; Ming Cao; Xin Mu; Guoliang Yang; Wei Xue; Yiran Huang; Haige Chen (Cell Biochemistry and Biophysics, 2015)

CCAAT-enhancer binding protein (C/EBP) β regulates insulin-like growth factor (IGF) 1 expression in porcine liver during prenatal and postnatal development - Yiting Tang; Kai Xiong; Ming Shen; Yulian Mu; Kui Li; Honglin Liu (Molecular and Cellular Biochemistry, 2015)

Resistance mechanisms and risk assessment regarding indoxacarb in the beet armyworm, Spodoptera exigua - Ming Gao; Wei Mu; Wei Wang; Chao Zhou; Xiuhuan Li (Phytoparasitica, 2014)

Aerosolized bovine lactoferrin reduces lung injury and fibrosis in mice exposed to hyperoxia - Hsiao-Ling Chen; Chih-Ching Yen; Shih-Ming Wang; Tung-Chou Tsai; Zi-Lun Lai; Jheng-Yue Sun; Willei Lin; Wu-Huei Hsu; Chuan-Mu Chen (BioMetals, 2014)

Spectrum analysis of wind profiling radar measurements - Zheng Ruan; Ruiqi Mu; Ming Wei; Runsheng Ge (Journal of Meteorological Research, 2014)

Intraperitoneal delivery of paclitaxel by poly(ether-anhydride) microspheres effectively suppresses tumor growth in a murine metastatic ovarian cancer model - Ming Yang; Tao Yu; Joseph Wood; Ying-Ying Wang; Benjamin C. Tang; Qi Zeng; Brian W. Simons; Jie Fu; Chi-Mu Chuang; Samuel K. Lai; T.-C. Wu; Chien-Fu Hung; et al. (Drug Delivery and Translational Research, 2014)

Resveratrol Pretreatment Attenuates the Isoflurane-Induced Cognitive Impairment Through its Anti-Inflammation and -Apoptosis Actions in Aged Mice - Xiao-min Li; Mai-tao Zhou; Xing-ming Wang; Mu-huo Ji; Zhi-qiang Zhou; Jian-jun Yang (Journal of Molecular Neuroscience, 2014)

Rice black-streaked dwarf virus genome segment S5 is a bicistronic mRNA in infected plants - Jian Yang; Heng-Mu Zhang; Lu Ying; Jing Li; Ming-Fang Lv; Li Xie; Pei-Pei Li; Xiao-Ya Liu; Dai Liang-Ying; Jian-Ping Chen (Archives of Virology, 2014)

Molecular characterization of sawtooth oak (Quercus acutissima) germplasm based on randomly amplified polymorphic DNA - Yuan-Yan Zhang; Yan-Ming Fang; Mu-Kui Yu; Xiao-Li Zhou (Plant Systematics and Evolution, 2013)

Whole exome sequencing identifies mutation of EDNRA involved in ACTH-independent macronodular adrenal hyperplasia - Jie Zhu; Liang Cui; Wei Wang; Xing-Yi Hang; A-Xiang Xu; Su-Xia Yang; Jing-Tao Dou; Yi-Ming Mu; Xu Zhang; Jiang-Ping Gao (Familial Cancer, 2013)

A correlation between acute kidney injury and myonecrosis after scheduled percutaneous coronary intervention - Min Zhang; Hao-yu Meng; Ying-ming Zhao; Zhi-wen Tao; Xiao-xuan Gong; Ze-mu Wang; Bo Chen; Zheng-xian Tao; Chun-jian Li; Tie-bing Zhu; Lian-sheng Wang; Zhi-jian Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Interactions between the P6 and P5-1 proteins of southern rice black-streaked dwarf fijivirus in yeast and plant cells - Jing Li; Jin Xue; Heng-Mu Zhang; Jian Yang; Ming-Fang Lv; Li Xie; Yuan Meng; Pei-Pei Li; Jian-Ping Chen (Archives of Virology, 2013)

Genetic diversity of two Tibetan macaque (Macaca thibetana) populations from Guizhou and Yunnan in China based on mitochondrial DNA D-loop sequences - Li-Jing Zhong; Ming-Wang Zhang; Yong-Fang Yao; Qing-Yong Ni; Jun Mu; Chong-Qing Li; Huai-Liang Xu (Genes & Genomics, 2013)

Molecular characterization and expression analysis of GlHMGS, a gene encoding hydroxymethylglutaryl-CoA synthase from Ganoderma lucidum (Ling-zhi) in ganoderic acid biosynthesis pathway - Ang Ren; Xiang Ouyang; Liang Shi; Ai-Liang Jiang; Da-Shuai Mu; Meng-Jiao Li; Qin Han; Ming-Wen Zhao (World Journal of Microbiology and Biotechnology, 2013)

HBV infection increases the risk of pancreatic cancer: a meta-analysis - Gang Luo; Ning-Bo Hao; Chang-Jiang Hu; Xin Yong; Mu-Han Lü; Bo-Jun Cheng; Yao Zhang; Shi-Ming Yang (Cancer Causes & Control, 2013)

Erratum to: UDP-glucuronosyltransferase 1A1 is the principal enzyme responsible for puerarin metabolism in human liver microsomes - Cheng-Feng Luo; Bin Cai; Ning Hou; Mu Yuan; Shi-Ming Liu; Hong Ji; Long-Gen Xiong; Wei Xiong; Jian-Dong Luo; Min-Sheng Chen (Archives of Toxicology, 2012)

UDP-glucuronosyltransferase 1A1 is the principal enzyme responsible for puerarin metabolism in human liver microsomes - Cheng-Feng Luo; Bin Cai; Ning Hou; Mu Yuan; Shi-Ming Liu; Hong Ji; Long-Gen Xiong; Wei Xiong; Jian-Dong Luo; Min-Sheng Chen (Archives of Toxicology, 2012)

Rosiglitazone inhibits angiotensin II-induced C-reactive protein production in human aortic endothelial cells through regulating AT1–ROS–MAPK signal pathway - Chun-Jie Han; Jun-Tian Liu; Ming Li; Mu Cui; Xiao-Ming Pang; Jun-Jun Mao; Xiao-Fang Liu (Inflammation Research, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Effects of 1,1,1-trichloroethane on enzymatic activity and bacterial community in anaerobic microcosm form sequencing batch reactors - Hui Li; Wei Zhang; Lu Li; Yong-Di Liu; Kuang-Fei Lin; Shu-Guang Lu; Bo-Zhong Mu; Xiao-Ming Du; Qiang Lu; Qian Zhang; Ting-Ting Shen; Bing-Zhi Li; et al. (Ecotoxicology, 2012)

Insulin-like growth factor 1 enhances the proliferation and osteogenic differentiation of human periodontal ligament stem cells via ERK and JNK MAPK pathways - Yan Yu; Jinquan Mu; Zhipeng Fan; Gang Lei; Ming Yan; Sainan Wang; Chunbo Tang; Zilu Wang; Jinhua Yu; Guangdong Zhang (Histochemistry and Cell Biology, 2012)

Sucrose treatment alters floral induction and development in vitro in gloxinia - Ming-Zhe Zhang; Li-Ling Wang; Dan Ye; Xi Chen; Zhi-Yi Wu; Xiao-Jia Lin; Wu-Jian Chen; Hong-Wu Bian; Ning Han; Mu-Yuan Zhu (In Vitro Cellular & Developmental Biology - Plant, 2012)

Optimisation of preparation conditions and properties of phytosterol liposome-encapsulating nattokinase - Xu-Yan Dong; Fan-Pi Kong; Gang-You Yuan; Fang Wei; Mu-Lan Jiang; Guang-Ming Li; Zhan Wang; Yuan-Di Zhao; Hong Chen (Natural Product Research, 2012)

Characterization of mitochondrial genome of Formosan sambar (Rusa unicolor swinhoei) - Chia-Hsuan Chen; Hsiu-Lin Huang; Mu-Tzu Chang; Li-Chia Chiang; Shih-Lin Cheng; Bing-Tsan Liu; Chih-Hua Wang; Ming-Che Wu; Mu-Chiou Huang (Biologia, 2011)

Resistance of Spodoptera exigua to ten insecticides in Shandong, China - Chao Zhou; Yongqiang Liu; Weili Yu; Zhaorong Deng; Ming Gao; Feng Liu; Wei Mu (Phytoparasitica, 2011)

No Association of Angiotensin I Converting Enzyme I/D Polymorphism with Domain-Specific Cognitive Function in Aged Men without Dementia - Mu-En Liu; Shih-Jen Tsai; Ti Lu; Cheng-Jee Hong; Ming-Chao Chen; Shoa-Lin Lin; Heng-Liang Yeh; Yan-Chiou Ku (NeuroMolecular Medicine, 2011)

Ovate family protein 1 as a plant Ku70 interacting protein involving in DNA double-strand break repair - Yung-Kai Wang; Wen-Chi Chang; Pei-Feng Liu; Mu-Kai Hsiao; Chueh-Tsun Lin; Shih-Ming Lin; Rong-Long Pan (Plant Molecular Biology, 2010)

A hybrid promoter-containing vector for direct cloning and enhanced expression of PCR-amplified ORFs in mammalian cells - Lei-ming You; Jun Luo; Ai-ping Wang; Gai-ping Zhang; Hai-bo Weng; Ya-nan Guo; Yun-chao Liu; Qiao-mu Li; Man Teng (Molecular Biology Reports, 2010)

Porcine lactoferrin as feedstuff additive elevates avian immunity and potentiates vaccination - Che-Ming Hung; Shinn-Chih Wu; Chih-Ching Yen; Ming-Fong Lin; Yi-Wen Lai; Yu-Tang Tung; Hsiao-Ling Chen; Chuan-Mu Chen (BioMetals, 2010)

Probiotic Lactobacillus casei Expressing Human Lactoferrin Elevates Antibacterial Activity in the Gastrointestinal Tract - Hsiao-Ling Chen; Yi-Wen Lai; Chua-Shun Chen; Te-Wei Chu; Willie Lin; Chih-Ching Yen; Ming-Fong Lin; Ming-Yu Tu; Chuan-Mu Chen (BioMetals, 2010)

Neuroscience in China 2000–2009: Introduction - Mu-Ming Poo (Science China Life Sciences, 2010)

Progress in neural plasticity - XiaoHui Zhang; Mu-Ming Poo (Science China Life Sciences, 2010)

Interaction between aluminum toxicity and manganese toxicity in soybean (Glycine max) - Zhong Bao Yang; Jiang Feng You; Mu Yun Xu; Zhen Ming Yang (Plant and Soil, 2009)

Variants of Lipopeptides Produced by Bacillus licheniformis HSN221 in Different Medium Components Evaluated by a Rapid Method ESI-MS - Yi-Ming Li; Namir I. A. Haddad; Shi-Zhong Yang; Bo-Zhong Mu (International Journal of Peptide Research and Therapeutics, 2008)

Completion of the sequence of rice gall dwarf virus from Guangxi, China - Heng-Mu Zhang; Xing Xin; Jian Yang; Jian-Ping Chen; Jian-Ming Wang; M. J. Adams (Archives of Virology, 2008)

Overexpression of the cucumber LEAFY homolog CFL and hormone treatments alter flower development in gloxinia (Sinningia speciosa) - Ming-Zhe Zhang; Dan Ye; Li-Lin Wang; Ji-Liang Pang; Yu-Hong Zhang; Ke Zheng; Hong-Wu Bian; Ning Han; Jian-Wei Pan; Jun-Hui Wang; Mu-Yuan Zhu (Plant Molecular Biology, 2008)

Efficient organogenesis and plantlet regeneration in the timber species Cunninghamia lanceolata (Lamb.) Hook - Mu-lan Zhu; Ji Wang; Yang Yu; Sheng-jun Liu; Zhi-ming Wei (In Vitro Cellular & Developmental Biology - Plant, 2007)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Optical Sensor for the Determination of Glucose Based on KIO4 Chemiluminescence Detection - Ming Li; Sang Hak Lee; Zun Ung Bae; Kwang Pill Lee; Yu Chul Park; Mu Sang Lee (Journal of Fluorescence, 2004)

Use of oligonucleotide fingerprinting and faecal DNA in identifying the distribution of the Chinese tiger (Panthera tigris amoyensis Hilzheimer) - Qiu-Hong Wan; Sheng-Guo Fang; Guo-Fu Chen; Zhang-Ming Wang; Ping Ding; Mu-Yuan Zhu; Kong-Shou Chen; Jiu-Hua Yu; Yue-Ping Zhao (Biodiversity and Conservation, 2003)